Mengintegrasikan Fatwa MUI No. 24 Tahun 2017 Dalam Upaya Edukasi Publik Terkait Ujaraan Kebencian Di Media Sosial - Elvi Sumanti; Sazali, Hasan; Nova Dwiyanti (STAI Bumi Silampari, 2025)
This research aims to explore the integration of MUI Fatwa No. 24 of 2017 in efforts to educate the public regarding hate speech on social media. Hate speech has become a serious problem that has a negative impact on social cohesion and the stability of society. The MUI fatwa, which emphasizes the importance of maintaining unity and avoiding division, provides a normative basis for dealing with this issue. This research analyzes the content and purpose of the fatwa, as well as the role of social media as a platform for disseminating information and potential hate speech. Through a qualitative approach, this study identifies effective public education strategies, including awareness campaigns and collaboration between the MUI, government and civil society. Apart from that, this research also examines the challenges faced in implementing fatwas and provides recommendations for increasing the effectiveness of education regarding hate speech. It is hoped that the results of this research can make a significant contribution to efforts to handle hate speech and strengthen the values of tolerance in society.